2021
DOI: 10.18699/vj21.075
|View full text |Cite
|
Sign up to set email alerts
|

Negative heterosis for meiotic recombination rate in spermatocytes of the domestic chicken Gallus gallus

Abstract: Benefits and costs of meiotic recombination are a matter of discussion. Because recombination breaks allele combinations already tested by natural selection and generates new ones of unpredictable fitness, a high recombination rate is generally beneficial for the populations living in a fluctuating or a rapidly changing environment and costly in a stable environment. Besides genetic benefits and costs, there are cytological effects of recombination, both positive and negative. Recombination is necessary for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Alternatively, a lower recombination rate in the F1 hybrids might be the result of negative heterosis. Malinovskaya et al [2021] found that F1 hybrids between 2 purebred breeds had a significantly lower recombination rate (2,950 cM) than the cockerels of both parental breeds, Russian Crested and Pervomai (3,150 cM and 3,350 cM, respectively). The authors explained the negative heterosis for the recombination rate by difficulties in homology matching between the DNA sequences of genetically divergent breeds.…”
Section: Interbreed Variation In the Recombination Ratementioning
confidence: 91%
“…Alternatively, a lower recombination rate in the F1 hybrids might be the result of negative heterosis. Malinovskaya et al [2021] found that F1 hybrids between 2 purebred breeds had a significantly lower recombination rate (2,950 cM) than the cockerels of both parental breeds, Russian Crested and Pervomai (3,150 cM and 3,350 cM, respectively). The authors explained the negative heterosis for the recombination rate by difficulties in homology matching between the DNA sequences of genetically divergent breeds.…”
Section: Interbreed Variation In the Recombination Ratementioning
confidence: 91%
“…Both single-and double-stranded breaks (SSB and DSB) are a common feature of cell karyotype studies after cannabis exposure [7][8][9][10]12,13,99]. It therefore becomes important in the present context to note that the epigenome plays an often determinative role in influencing or selecting the site of DNA breakage generally [118][119][120][121][122][123][124][125][126][127][128][129][130][131], during meiotic crossing over [132][133][134][135][136][137][138][139], in the immune gene hypervariable region [140][141][142][143][144][145][146], and in oncogenic pathways [120,123,124,[147][148][149][150][151][152][153]…”
Section: Epigenomic Impacts On Dna Breakage Sitesmentioning
confidence: 99%